(+3)+(-2)+(-5)=
(-2)-(+1)-(+5)=
(+4)+(-2)-(+3)=
(+5)-(-3)-(-1)
(+4)+(-6)-(+7)-(-6)+(+7)=
(-3)-(-5)+(-6)+(+8)-(-4)=
+(-3+8)-(-3+8)+(5-6)=
-(-3-1)-(-6+4-1)-6-(-3+2)=
preciso só dá resposta cálculo não
Respostas
respondido por:
2
Resposta:
-4
-8
1
9
4
8
-1
2
Explicação passo-a-passo:
3-2-5= -4
-2-1-5= -8
4-2-3= 1
5+3+1= 9
4-6-7+6+7= 4
-3+5-6+8+4= 8
-3+8+3-8+5-6= -1
+3+1+6-4+1-6+3-2= 2
biaahgomes0136:
obrigada
Perguntas similares
5 anos atrás
5 anos atrás
5 anos atrás
8 anos atrás
8 anos atrás
8 anos atrás
9 anos atrás
9 anos atrás